Conventional And Cognitive Radio Based Disaster Response Networks, A Comparative Study - AlAqad, Khaled F.; M.A., Burhanuddin; Harum, Norharyati; Ali, Waleed Saeed Mahmoud (Semnan University, Center of Excellence in Nonlinear Analysis and Applications, 2020)
The need for the deployment of reliable and efficient telecommunication systems in extreme emergency scenarios such as disaster response networks imposes a set of emerging unusual communication and routing challenges and obstacles that questions the performance of existing traditional and commercial telecommunication systems and networks in such scenarios, the revolution of telecommunication and networks industry witnessed the development of enormous telecommunication and networking services and systems that shaped their implementations in various domains of applications , in this paper, we study most of these communication standards in terms of their pros and cons, we also analyze the potentials of these standards in for Disaster Response networks in comparison with Cognitive Radio technology that has distinct capabilities and functionalities that enabled such a technology to be highly applicable for such harsh and unexpected scenarios